LEGAL ANALYSIS OF TRANSFER OF SHARES TO PARTIES OTHER THAN THE HEIRS OF SHARE OWNERS WHICH CAUSE ACTS UNLAWFUL (CASE STUDY OF MEDAN DISTRICT COURT DECISION NO. 552/PDT.G/2018/PN.MDN) - Nadeak, Sugianto SP; Sirait, Ningrum Natasya; Robert, Robert (NOMOI Law Review, 2024)
Shares are movable objects so that shareholders can transfer shares to other parties by fulfilling the requirements for transfer of rights as stipulated in Law Number 40 of 2007 concerning Limited Liability Companies (UUPT). Shares can be transferred to the heirs of the shareholder if the shareholder dies. The transfer of shares due to inheritance is regulated in Article 57 paragraph (2) of the UUPT. This provision confirms that shares are an object of inheritance. Inheritance for Christians is regulated in civil law provisions (KUH Perdata). Article 833 of the KUH Perdata stipulates that the right to ownership of the heir is legally transferred to the heirs. This provision states that the heirs have rights to the shares owned by the heir so that if the shares are transferred or distributed to other parties without the consent of the heirs, it is a form of unlawful act. This research is normative legal research with a statute approach and case study. The results of the study found that limited liability companies secretly transferred shares by distributing shares owned by deceased shareholders to other parties without the consent of the shareholder's heirs as in the Medan District Court Decision Number: 552/Pdt.G/2018/PN.Mdn. Based on the evidence in the trial, the Judge in the decision stated that the limited liability company's actions in distributing shares owned by deceased shareholders to other parties without the consent of the heirs was an unlawful act because according to the UUPT, limited liability companies are not shareholders so that limited liability companies do not have the right and capacity to distribute the shares